Role of Individual Academics and International Universities in Health Research in Nepal - Simkhada, P; van Teijlingen, E (Nepal Journal of Epidemiology, 2012)
Nepal has made progress in health sciences and medical education over the past decade. We believe that there is a need in Nepal for a greater research emphasis on mixed-methods approaches, qualitative research, critical appraisal & systematic reviewing and health economics. Specifically to the discipline of epidemiology, Nepal should consider establishing more and better epidemiological studies, the kind of population-based studies that can identify risk factors, track changes over time at a population level over the decades to come. We know how important such long-term research is but we are also painfully aware how expensive this kind on long-term research can be. DOI: http://dx.doi.org/10.3126/nje.v2i2.6572 Nepal Journal of Epidemiology 2012;2(2):179-81